2017
DOI: 10.1177/2192568217699378
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Impact, and Risk Factors for 30-Day Wound Complications Following Elective Adult Spinal Deformity Surgery

Abstract: Study Design:Case-control study.Objective:To determine the incidence, impact, and risk factors for wound complications within 30 days following elective adult spinal deformity surgery.Methods:Current Procedural Terminology and International Classification of Diseases, Ninth Edition, diagnosis codes were used to query the database for adults who underwent spinal deformity surgery from 2010 to 2014. Patients were separated into groups of those with and without wound complications. Univariate analysis and multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…16 Elevated ASA class has also previously been reported as a risk factor for postoperative complications in spinal fusion surgery in other studies. 16,[18][19][20] Our findings suggest an association between incurring increased complications and extended operative times, which is corroborated by previous studies identifying longer operation time as predictive of developing postoperative complications. [18][19][20] Our finding that smoking is associated with surgical delay is not surprising considering the myriad of deleterious effects smoking has on general health conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 Elevated ASA class has also previously been reported as a risk factor for postoperative complications in spinal fusion surgery in other studies. 16,[18][19][20] Our findings suggest an association between incurring increased complications and extended operative times, which is corroborated by previous studies identifying longer operation time as predictive of developing postoperative complications. [18][19][20] Our finding that smoking is associated with surgical delay is not surprising considering the myriad of deleterious effects smoking has on general health conditions.…”
Section: Discussionsupporting
confidence: 90%
“…16,[18][19][20] Our findings suggest an association between incurring increased complications and extended operative times, which is corroborated by previous studies identifying longer operation time as predictive of developing postoperative complications. [18][19][20] Our finding that smoking is associated with surgical delay is not surprising considering the myriad of deleterious effects smoking has on general health conditions. 21,22 This association corresponds with our other findings that advanced age and an elevated ASA class, both factors which are indicative of poorer health, are also more likely to lead to a surgical delay.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al reported a decrease in wound infection rate after spinal deformity surgery between 2010 and 2014, from 3.3% to 2.4%. 11 Likewise, Passias et al found a significant decrease in postoperative complications (from 26.7% to 8.6%; p < 0.001) for patients over 75 years of age undergoing deformity surgery between 2003 and 2012, even though the case complexity was found to actually have increased. 17 Another potential important bias results from the studies by Elder et al 5 and Ishida et al, 9 both stemming from the same institution.…”
Section: Discussionmentioning
confidence: 93%
“…Three studies report cumulative incidence of wound complications following ≥3 level posterior spine fusion ( Table 1 ). 15 17 Mean ages ranged from 59 to 64 years with the proportion of males ranging from 39% to 68%. Follow-up times for 2 studies were 1 month and 2 years.…”
Section: Resultsmentioning
confidence: 99%